Update of the operational production system and organizational structure as the basis of the innovative development of the construction enterprise - Mudra, M.S. (Ways to Improve Construction Efficiency, 2023)
The article presents a formalized economic-mathematical model that makes it possible to estimate the effect of the joint introduction of information modeling in construction and an integrated project management system to solve the tasks of extracting from the overall effect of the enterprises' activity the share that arises as a result of the introduction of innovations. It was determined that the analysis of empirical data is a mandatory condition for the formation of proposals for improving the activities of economic entities, in general, and the development of direct measures within the limits of individual functional types of activity, in particular. In order to obtain up-to-date and verified information about the activities of the studied enterprises, the work pays attention to the analysis of trends in the development of domestic construction. An analysis of the destabilizing effect of factors on the economic security of these enterprises is presented using the approaches and indicators of the rating assessment of Doing Business business conditions. This approach allows detailing the general state of the business environment at the macro level and explaining the deep processes of the response of the enterprise management system to the challenges of modernity, which form a certain security environment at different levels of management of complex socio-economic systems. A model of flexible management of the enterprise has been developed to ensure its economic security, which is built on the basis of two-component neural network diagnostics, taking into account the needs of the main stakeholders and determining the internal and external factors influencing the enterprise's activities. The model allows management to determine the most relevant list of management decisions and take into account external and internal threats, which ensures an increase in the level of economic security of the enterprise due to sufficient flexibility of the management system and timely response to current threats.